Covid-19 in the Caribbean: lessons learned from the ongoing international medical and scientific cooperation - Dabor Resiere; Hossein Mehdaoui; Hedda Dyer; Cyrille Chabartier; André Cabié; Jocelyn Inamo; Keats Compton; Rémi Neviere; Bruno Megarbane; Hatem Kallel (BMC, 2021)
Abstract The coronavirus disease (Covid-19) crisis presents as human, social and economic challenges. The advent of Covid-19, unfortunate as it is, has highlighted the need for close medical cooperation between states. Medical cooperation is the key counter to fight against the Covid-19 pandemic.